Synthesis Process of Stable Bafeo4 by Dry Method - EL MAGHRAOUI, Abdellatif; ZEROUALE, Abdelaziz; IJJAALI, Mustapha (International Journal of Chemistry and Materials Research, 2015)
Ferrate (VI) alkalis are the best known and best studied. The importance of their study is due to their increasingly diverse and innovative applications. The aim of this work is to prepare stable at ambient BaFeO4, to study and optimize the key parameters influencing the performance of the oxidation of iron (III) into iron (VI) and to monitore its degradation over time in order to minimize the cost and improve the production of ferrate (VI) for their interest in the water treatment.. the synthesis of the phase was carried out by dry processing, using the reaction Ba3 (Fe(OH)6)2, H2O, and Ba(OH)2 at a temperature of 850 ° C under flowing oxygen for a period of 12 hours with a ratio of Ba / Fe = 3. The result was characterized by UV spectrophotometer, measuring the optical density at the wavelength of 507 nm.